2021
DOI: 10.1016/j.jamcollsurg.2021.08.679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wound Contamination on Outcomes of Abdominal Wall Reconstruction Using Acellular Dermal Matrix: 14-Year Experience with More than 700 Patients

Abstract: Background Patients with contaminated/dirty-infected defects are at high risk for postoperative complications after abdominal wall reconstruction (AWR). We evaluated outcomes of AWR using acellular dermal matrix (ADM) for mesh reinforcement and identified predictors of hernia recurrence (HR), surgical site occurrences (SSOs), and surgical site infections (SSIs). Study Design We conducted a retrospective cohort study of patients who underwent AWR using A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…These treatments include, among others, burn treatments, hernia repair, breast reconstruction, etc. [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Moreover, there are several reports on the use of ADMs in gynaecological reconstructive surgery [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These treatments include, among others, burn treatments, hernia repair, breast reconstruction, etc. [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Moreover, there are several reports on the use of ADMs in gynaecological reconstructive surgery [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of prior experience with AWR, fellows were generally trained on the AWR techniques that were consistently performed at the authors' institution. [10][11][12] Patient selection was based on patient availability and did not follow any selection criteria. A trainee had to have complete autonomy in preoperative, intraoperative, and postoperative care and decision-making to be considered the operative surgeon for a case.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…After analyzing patients who had at least 36 months of postoperative follow-up, a report revealed that ADMs can provide durable long-term outcomes in complex abdominal wall reconstruction with hernia recurrence rates similar to those for synthetic meshes, and achieve lower infection and mesh explantation rates than those reported for synthetic meshes [92]. Moreover, relevant studies have shown that ADM can reduce complications for patients with multiple comorbidities and for those with abdominal wall reconstructions in contaminated wound environments [93,94]. In addition, based on a similar principle of ADM application in abdominal wall reconstruction, ADM has also exhibited good application outcomes in chest wall repair.…”
Section: Applications In Abdominal/chest Wall Repairmentioning
confidence: 99%